Placenta Accreta Spectrum: Risk Factors for Unplanned Immediate Hysterectomy in Planned Uterine Preservation Surgery - Friedrich, Lior; Mor, Nitzan; Weissmann-Brenner, Alina; Kassif, Eran; Friedrich, Shakad Noah; Weissbach, Tal; Castel, Elias; Levin, Gabriel; Meyer, Raanan (American Journal of Perinatology, 2024)
Placenta accreta spectrum (PAS) is a term used to describe trophoblast invasion into the uterine wall. The condition can be fatal at labor due to a lack of spontaneous separation of the placenta from the uterine wall, leading to severe hemorrhage. In this study, we aim to evaluate preoperative risk factors for unplanned immediate hysterectomy in PAS uterine-preserving surgeries.Preoperative parameters of women who underwent successful uterine-preserving surgery were retrospectively compared with those who underwent an unplanned immediate hysterectomy during these surgeries. A multivariable regression analysis was conducted to identify independent factors associated with unplanned immediate hysterectomy.Overall, 238 were included in the study's cohort. A total of 86.2% underwent successful uterine-preserving surgery, and 13.8% underwent an unplanned immediate hysterectomy. The number of previous cesarean deliveries (CDs) and the proportion of women with grade 3 preoperative PAS was significantly lower among the successful uterine-preserving group. The proportion of preoperative ultrasound lacunae detection, the number of lacunae observed, loss of clear zone detection, the length of clear zone loss, the proportion of retroplacental hypervascularity, bridging vessels detection, and bladder involvement were significantly lower in the successful uterine-preserving group. In a multivariable regression analysis, the presence of lacunae and loss of clear zone were independently associated with unplanned cesarean hysterectomy (adjusted odds ratio [aOR] = 3.18 [95% confidence interval (CI): 1.11–11.6], p = 0.047, and aOR = 3.67 [95% CI: 1.3–13.2], p = 0.025, respectively].Preoperative assessment of the applicability of a uterine-preserving surgery may be performed using the ultrasound parameters reported in this study.
Keywords: placenta accreta spectrum; uterine-preserving surgery; hysterectomy; conservative management; sonographic characteristics